Pengaruh Faktor Psikologis Terhadap Peningkatan Prestasi Atlet: Literature Review pada Studi Psikologi Olahraga - Muhammad Hikmal Akbar; Indra Yusuf; Nabile Anggoro Waskito; Putra Bangun Airlangga; Wisanggeni Akbar Priambudi (GLOBAL SCIENTS PUBLISHER, 2026)
This study aims to determine the psychological influence on athletes while analyzing psychological factors that contribute to performance improvement through a System Literature Review (SLR). The method used in this study is a qualitative method with a System Literature Review (SLR) type using a systematic article search through Publish or Perish and Google Scholar. In journals with keywords that facilitate search understanding such as: